Evaluation of Anti-tumor Properties of Herbal Formulations against Ehrlich Ascites Solid Tumor Mice Model - Kumar, Manish (International Journal of Pharmaceutical & Biological Archive, 2023)
Saraca indica (Ashoka) is an important plant belonging to the family Fabaceae. It essentially contains glycosides, tannin, saponin, flavonoids, and sterol. It possesses a variety of activities such as analgesic, antipyretic, fungitoxic, anthelmintic, antidiabetic, larvicidal activity, antimicrobial activity, central nervous system depressant activity, antiulcer activity, anti-cancer, and anti-inflammatory activity. The anticancer principle from S. indica flowers indicated 50 percent cytotoxicity (in vitro) in Dalton’s lymphoma ascites and Sarcoma-180 tumor cells at a concentration of 38 mug and 54 mug, respectively, with no activity against normal lymphocytes but preferential activity for lymphocytes derived from leukemia patients. A new plant is also taken as they have no reported activity for in vivo in cancer. One such plant is Solanum xanthocarpum Schrad. and Wendl. (Family: Solanaceae). Various therapeutic properties are attributed to it, particularly in the cure of asthma, chronic cough, and catarrhal fever. Plant contains alkaloids, sterols, saponins, flavonoids, and their glycosides and also carbohydrates, fatty acids, and amino acids. The exact mechanism of action of Kantkari is still unknown due to not reported yet, so the present study was designed to investigate the anti-tumor potential of herbal drugs (Ashoka and Kantkari) against Ehrlich ascites solid tumor mice model. Solid tumors were induced by injecting Ehrlich ascites carcinoma (EAC) cells (15 × 106/mice) subcutaneously in right hind limb. Treatment with drugs (Ashoka and Kantkari) showed significant decrease in body weight, solid tumor volume, and tumor weight in EAC tumor-bearing mice at a dose of 400 mg/kg and 200 mg/kg, respectively. Ashoka increased the mean survival time of tumor-bearing mice and percentage increase in life span (was found to be 90.53% and Kantkari is 88.33%, respectively, which is lower than the standard drug Vincristine but Kantkari shows that the tumor inhibition is more significant than Ashoka. Results of with hematoxylin and eosin and immunohistochemistry explained the possible mechanism of action of drugs (Ashoka and Kantkari). Decreased expression of vascular endothelial growth factor indicated the anti-angiogenic property. Immunochemical analysis of solid tumor showed increased expression of caspase-3 suggested that drugs (Ashoka and Kantkari) induced apoptosis in tumor cells. Findings of the present study explored the possible anti-tumor properties of drugs (Ashoka and Kantkari) and can be room for further evaluations in clinical studies.